THE ROLE OF LOCAL GOVERNMENT AS SOCIAL CHANGE AGENT IN CIPAGERAN DAIRY CENTER CIMAHI CITY - Dede Sri Kartini; Dicky Febriansyah Rokhmat (Program Studi Ilmu Pemerintahan FISIP Universitas Galuh, 2023)
The distribution of poor families in North Cimahi Subdistrict is the highest with 39.1% with Cipageran Village having the most farmer communities because it has a group of breeders in the Cipageran Dairy Center. Overcoming this, the Cimahi City Government made social change efforts through community empowerment program interventions, however, there were a number of obstacles, such as rejection from the community and programs that were not on target. The purpose of this study was to describe the role of the Cimahi City Government as agents of social change in Cipageran Dairy Center. The research method uses descriptive with a qualitative approach. Data collection techniques using the method of observation and literature study. The selected informants were the Head of Research and Development, representatives of the Cipageran Dairy Center Management, representatives of the Women Farmers Group and representatives of researchers who contributed to the Cipageran Dairy Center. While the data analysis technique is done descriptively. The results of the study show that the Cimahi City Government as an agent of social change as a regulator has issued a number of regional head regulations and planning documents. The role as a dynamicator is carried out by developing value chains, pilot projects and developing eco-tourism in Cipageran. Role as a facilitator by placing extension workers for breeders and milk processors and encouraging universities to implement Community Service Program in Cipageran and role as a catalyst to activate eco-tourism in Legok Awi Market.